2021
DOI: 10.1039/d1ra00359c
|View full text |Cite
|
Sign up to set email alerts
|

Biologically guided isolation and ADMET profile of new factor Xa inhibitors fromGlycyrrhiza glabraroots usingin vitroandin silicoapproaches

Abstract: Biologically guided isolation of new factor Xa inhibitors from Glycyrrhiza glabra roots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 72 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Then, optimization through energy minimization and determination of ionization states at the specified pH (7 ± 2.0) were conducted. The default parameters were used for ADME prediction in the normal mode ( Ibrahim et al, 2021 ). The following ADME properties were predicted, including partition coefficient (QPlogP octanol/water), predicted aqueous solubility (QPlogS), predicted brain/blood partition coefficient (QPlogBB), gut–blood brain barrier (QPPCaco), predicted IC 50 value for blockage of HERGK + channels (QPlogHERG), and predicted value of binding to human serum albumin (QPlogKhsa) ( Toppo et al, 2021 ; Tan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, optimization through energy minimization and determination of ionization states at the specified pH (7 ± 2.0) were conducted. The default parameters were used for ADME prediction in the normal mode ( Ibrahim et al, 2021 ). The following ADME properties were predicted, including partition coefficient (QPlogP octanol/water), predicted aqueous solubility (QPlogS), predicted brain/blood partition coefficient (QPlogBB), gut–blood brain barrier (QPPCaco), predicted IC 50 value for blockage of HERGK + channels (QPlogHERG), and predicted value of binding to human serum albumin (QPlogKhsa) ( Toppo et al, 2021 ; Tan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Glabridin is selective as the effective compound to inhibit FXa selectively with an IC 50 value of 35.3 μM. 137 Glabridin shows protective activity against SARS CoV-2 with an IC 50 value of 2.5 μM. 138 Clinically, S. aureus has been developed to acquire multidrug resistance, and it has become a critical pathogen in hospital and community infections.…”
Section: Toxicology and Clinical Applicationsmentioning
confidence: 99%
“…In a very recent study on pharmacokinetic profiling of compound such as 7,4′-dihydroxyflavone, formononetin, 3-R-glabridin, isoliquiritigenin, liquiritin, naringenin 5-O-glucoside, 3,3′,4,4′-tetrahydroxy-2-methoxychalcone, liquiritinapioside, isoliquiritigenin-4′-O-β-D-apiosylglucoside and isoliquiritigenin-4-O-β-D-apiosylglucoside. It was found that out of them glabridin and 7-hydroxy-4′-methoxyisoflavone exhibits 100% of oral absorption to develop orally active direct FXa inhibitors ( Ibrahim et al, 2021 ).…”
Section: Pharmacokinetic Profilementioning
confidence: 99%